Między tekstem kultury a praktyką kliniczną. Narracje o psychiatrach a aktualne problemy dyscypliny - Hoss, Anna Róża (Załącznik Kulturoznawczy, 2020)
Narratives about psychiatry and psychiatrists, which appear in texts of culture, are clearly negative. Nevertheless, media images are the main source of common knowledge concerning the field. Several strategies of stereotyping psychiatrists in movie images can be distinguished. Social attitudes towards psychiatry, including these present among medical specialists, as well as psychiatrists themselves, reflect similar areas of devaluation. These problem fields are a valuable source of information about current problems within the discipline, and the condition of the cultural reality in which it is immersed.